2020
DOI: 10.1002/bjs.11306
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Norwegian survival prediction model in trauma (NORMIT) in Swedish trauma populations

Abstract: Background Trauma survival prediction models can be used for quality assessment in trauma populations. The Norwegian survival prediction model in trauma (NORMIT) has been updated recently and validated internally (NORMIT 2). The aim of this observational study was to compare the accuracy of NORMIT 1 and 2 in two Swedish trauma populations. Methods Adult patients registered in the national trauma registry during 2014–2016 were eligible for inclusion. The study populations comprised the total national trauma (NT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…A porting of NORMIT to a Finish trauma population showed a ROC-AUC of 0.83 (8) and ROC-AUC ranging 0.93-0.98 porting NORMIT 1 and 2 to a Swedish trauma population (35). Our TQIPID-based model achieved 0.971 ROC-AUC when porting, thus indicating similar performance.…”
Section: Modelsupporting
confidence: 52%
“…A porting of NORMIT to a Finish trauma population showed a ROC-AUC of 0.83 (8) and ROC-AUC ranging 0.93-0.98 porting NORMIT 1 and 2 to a Swedish trauma population (35). Our TQIPID-based model achieved 0.971 ROC-AUC when porting, thus indicating similar performance.…”
Section: Modelsupporting
confidence: 52%
“…Our findings and conclusion contrast Norwegian models (Norwegian survival prediction model in trauma [NORMIT and NORMIT 2]), which include ASA-PS, which have outperformed TRISS in mortality prediction. 18,[29][30][31] However, these models have only been validated in Finland and Sweden, and differences in trauma patient populations, the patterns of injury (eg, penetrating trauma), and prevalence of comorbidities may explain the discrepancies compared to our United States study population. The Norwegian study reported a penetrating injury rate of 9.1% and an ASA-PS score of 1 in 74% of patients, compared to 27.1% and 19% in this study, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…The inclusion criteria in SweTrau have been described previously 6 . The registry is based on the revised Utstein Trauma Template, which is the current European core dataset 17 , and has registered patients in Sweden since 2011.…”
Section: Methodsmentioning
confidence: 99%
“…RAM has become the standard method for measuring and comparing hospital performance in trauma populations, and is widely used in North America and Europe 2–4 . The Norwegian survival prediction model in trauma (NORMIT) was developed from a single level 1 trauma centre population in Norway, and externally validated in Finnish 5 and Swedish (NORMIT and the recently updated NORMIT 2) 6 trauma populations. The NORMIT models demonstrated adequate prediction of mortality in Swedish trauma centre populations but performed poorly in mixed populations of patients admitted to all hospital types 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%